Anogenital System and HPV-Related Lesions in Women: Anatomy, Pathophysiology, and Screening - Bornaun, Teymur (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Aims: This chapter aims to provide a comprehensive overview of the anatomy, physiology, and histology of the cervix and anal canal in women. It further explores the role of the Human Papilloma Virus (HPV) in the pathogenesis of cervical and anal carcinogenesis, emphasizing the epidemiology, oncogenic mechanisms, and associated lesions. Study Design: The chapter is structured as a detailed review of current literature, integrating anatomical, physiological, and pathological aspects with epidemiological data on HPV-related cancers. Key areas include the anatomy and histology of the cervix and anal canal, HPV virology, the epidemiology of HPV-related cancers, and the mechanisms of HPV-induced oncogenesis. Place and Duration of Study: The literature review covers studies published globally, focusing on research from the last two decades, with particular attention to studies from 2000 to 2024. Results: The findings highlight the significant impact of HPV on cervical and anal cancer development. The chapter outlines the progression from HPV infection to carcinogenesis, identifying the critical role of specific HPV strains. It also discusses the screening and vaccination strategies currently in place to prevent HPV-related lesions and their effectiveness in reducing cancer incidence. Conclusion: HPV plays a central role in the development of cervical and anal cancers in women. Understanding the anatomical and physiological aspects of the cervix and anal canal, along with the pathophysiology of HPV, is crucial for developing effective prevention and treatment strategies. The chapter concludes with recommendations for improving screening and vaccination programs to reduce the burden of HPV-related cancers.